Optimizing Worker Potential: Integrating Multiple Intelligences to Enhance Workplace Performance and Wellbeing - Kusumah, Alum; Sulistyandari (International Journal of Applied Management and Business, 2024)
Purpose – This paper investigates how intellectual quotient (IQ), emotional quotient (EQ), and spiritual quotient (SQ) influence workplace behaviors and outcomes. Historically research concentrated on IQ, but now recognizes intelligence as multidimensional. Beyond IQ, EQ involves emotional skills, while SQ relates to finding meaning.Methodology/approach – The systematic review follows PRISMA guidelines. Multiple databases were searched for relevant studies published between 2021-2022. Studies were screened based on predefined eligibility criteria. Data was extracted using a standardized form and analyzed through a narrative synthesis approach focused on patterns regarding the comparative and combined effects of IQ, EQ and SQ on work factors.Findings – IQ strongly predicted technical proficiency but had limits in interpersonal contexts. EQ uniquely improved leadership, teamwork, stress management, and customer service. SQ enhanced motivation, ethics, resilience, and well-being. Combined, IQ, EQ, and SQ synergistically optimized achievement, conduct, adaptation, and satisfaction across diverse occupational roles.Novelty/value – This review provides a comprehensive, up-to-date synthesis of empirical evidence demonstrating the multidimensional impacts of IQ, EQ, and SQ on workplace effectiveness. The insights can guide employee selection, training, and management practices focused on cultivating intellectual, emotional, and spiritual competencies in balance